Versatile route to core–shell reinforced network nanostructures. Issue 32 (6th August 2019) - Rusch, Pascal; Niemeyer, Fabian; Pluta, Denis; Schremmer, Björn; Lübkemann, Franziska; Rosebrock, Marina; Schäfer, Malte; Jahns, Mandy; Behrens, Peter; Bigall, Nadja C.
Abstract : Nanocrystal based networks are surrounded and reinforced by a continuous metal oxide shell. Abstract : In this work we present the generation of new core–shell network nanostructures of macroscopic dimensionality by a two-step process analogous to the seeded-growth method in colloidal nanoparticle modification. The nanoparticle-based core network is assembled first and in a separate second step it is coated with a continuous metal oxide shell by sol–gel methods. The interparticle contact of the nanoparticles comprising the core network is kept intact throughout the process. By analyzing the local elemental distribution, the shells can be shown to be homogeneous over the macroscopic network monolith. The shell network can be used to considerably reinforce the mechanical strength of the final core–shell network structure.